Factors affecting sponsorship objectives: a systematic review - Tan, Aaron Jia Jin (2017)
Sponsorship has been increasing steadily over the last 20 years and has become an important tool a marketer when it comes to achieving its brand objectives and increasing its brand equity. As the popularity of sponsorships increases, the cost of sponsoring has also increased to commensurate with the rise in demand. Thus, it is becoming increasingly important for marketer’s to decide if a sponsorship plan is working or are company’s simply blowing through money with very little return on investment. Since there is no industry-recognised standard that has been accepted to accurately evaluate sponsorship effectiveness, this paper looks at some of the important sponsorship objectives a marketer wants to achieve when sponsoring an event such as increasing purchase intention, improving attitude towards the sponsor, improving brand recall and improving brand loyalty and the factors that affect them. The aim is to find some insight on how marketers can improve sponsorship effectiveness. Research studies from 1997 to 2017 on sponsorship were reviewed. The conclusions are that it is important for marketer’s to research on events thoroughly and sponsor events which are a good fit to the brand’s products. The second finding is that the more highly-involved the spectator, the more receptive they are to sponsorship and hence the more likely that they will buy a sponsor’s product.